Effects of NOx, SO2 and RH on the SOA formation from cyclohexene photooxidation. (February 2019) - Liu, Shijie; Jiang, Xiaotong; Tsona, Narcisse T.; Lv, Chen; Du, Lin
Abstract: We performed a laboratory investigation of the secondary organic aerosol (SOA) formation from cyclohexene photooxidation with different initial NOx and SO2 concentrations at low and high relative humidity (RH). Both SOA yield and number concentration first increase drastically and then, decreased when the [VOC]0 /[NOx]0 ratio changed from 30 to 10 and from 10 to 3. Though the presence of SO2 could increase the SOA number concentration, the SOA yield could only increase under [VOC]0 /[NOx]0  = 10 and high RH, and [VOC]0 /[NOx]0  = 3 and low RH experimental conditions, while decreasing under [VOC]0 /[NOx]0  = 10 and low RH conditions. In the presence of SO2, the high RH and high NOx conditions were keys to efficient sulfate formation and could promote the SOA formation. The chemical composition of SOA was characterized using hybrid quadrupole-orbitrap mass spectrometer equipped with electrospray ionization (ESI-Q-Orbitrap-HRMS), and few organosulfates were identified. A visible enhancement of organosulfates and the formation of high molecular weight organic compounds were observed at high RH conditions, and this seemed to be the reason for the SOA yield increase at high RH. Graphical abstract: Highlights: Combined effects of NOx, SO2 and RH on cyclohexene SOA formation were studied. High RH and NOx promote organosulfates formation. Organosulfates formation mechanism from cyclohexene was proposed.